Optical Microresonators Theory, Fabrication, and Applications - Heebner, John. (Springer Series in Optical Sciences,, 2008)
This book explains why microresonators came to be important components in the photonic toolbox. While functionally similar to the Fabry-Perot, microring resonators offer a planar nature which is naturally compatible with monolithic microfabrication technologies. In these chapters lie the principles required to characterize, design, construct, and implement microresonators as lasers, amplifiers, sensors, filters, demultiplexers, switches, routers, and logic gates. Additionally, much like quantum dots and photonic crystals, it will be shown how microresonators offer an alternative method for creating engineerable materials with designer linear and nonlinear responses tailored for advanced functionalities operating at ultrafast speeds and compact scales. This is the first detailed text on the theory, fabrication, and applications of optical microresonators, and will be found useful by both graduate students and researchers. With an emphasis on building intuition with distilled equations and graphical illustration, readers will find it to be both an effective learning tool and technical reference.